Worker compensation schemes and product market competition - Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2020)
We analyze product market competition between firm owners where the risk-neutral workers decide on their efforts and, thereby, on the output levels. Various worker compensation schemes are compared: a piece-rate compensation scheme as a benchmark when workers' output performance is verifiable, and a contest-based as well as a tournament-based compensation scheme when it is only verifiable who the best performing worker is. According to optimal designs, all the considered compensation contracts lead to an equal market outcome. Therefore, it depends decisively on the relative costs of organizing a monitoring device, a contest, or a tournament whether the one or the other compensation scheme should be implemented.
urn:nbn:de:bsz:21-dspace-972820
Keywords: C72; L22; M52; 330; worker compensation schemes; piece rates; contests; tournaments; product market competition